Long-term durability properties of alkali-activated binders containing slag, fly ash, palm oil fuel ash and rice husk ash. (10th August 2020) - Hossain, M.M.; Karim, M.R.; Elahi, M.M.A.; Islam, M.N.; Zain, M.F.M.
Highlights: Durability of alkali-activated binders named AAB-1 and AAB-2 has been investigated. Chloride ion penetration and carbonation of AAB-1 and AAB-2 are discussed. Corrosion resistance and drying shrinkage of AAB-1 and AAB-2 are illustrated. Durability of AAB-1 and AAB-2 binder are compared with the ordinary cement mortar. Results are compared with previous studies and conclusions are made. Abstract: This study has investigated the chloride ion penetration, carbonation, corrosion resistance, and drying shrinkage of alkali-activated binders (AABs) that include: (i) AAB-1 being produced from slag, palm oil fuel ash, and rice husk ash while (ii) AAB-2 is composed of slag, fly ash, and rice husk ash, both being activated by 2.5 M sodium hydroxide solution. Chloride ion penetration result revealed a slightly higher value in AAB-1 and AAB-2 mortars than the reference ordinary Portland cement (OPC) mortar when tested in NaCl solution for 270 days. Carbonation depth of AAB mortar was found more than 4.3 times higher than the OPC mortar exposed to accelerated carbonation for 540 h. Half-cell potential readings revealed a similar corrosion resistance for all the mortars after 270 days. However, AAB-1, AAB-2 and OPC mortars showed a shrinkage value of 833, 782 and 474 microstrain, respectively, after 270 days. Therefore, above-mentioned pozzolans with NaOH cannot be recommended to use (solely) as an alternative to OPC in terms of the durability aspects investigated in this study.